2014
DOI: 10.1158/0008-5472.can-13-1750
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at Ser-181 of Oncogenic KRAS Is Required for Tumor Growth

Abstract: KRAS phosphorylation has been reported recently to modulate the activity of mutant KRAS protein in vitro. In this study, we defined S181 as a specific phosphorylation site required to license the oncogenic function of mutant KRAS in vivo. The phosphomutant S181A failed to induce tumors in mice, whereas the phosphomimetic mutant S181D exhibited an enhanced tumor formation capacity, compared with the wild-type KRAS protein. Reduced growth of tumors composed of cells expressing the nonphosphorylatable KRAS S181A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 40 publications
7
63
0
Order By: Relevance
“…53 Most importantly, we recently reported that inhibition of KRAS phosphorylation impaired tumor growth. 54 This is in agreement with the data presented here as we show that the cell lines with higher interaction of oncogenic KRAS with p110α ( Fig S9) and with HNRNPA2B1 (Fig 2) were the ones harboring phosphorylated KRAS (Fig 6) at serumlimiting conditions. Related to this point, in the current work we also proved that KRAS phosphorylation at Ser181 was sufficient to recruit more HNRNPA2B1 to the cytoplasmic cell membrane (Fig 6), thus suggesting that the higher cytoplasmic accumulation that exhibited KRAS-dependent PDAC was a consequence, instead of a cause, of its increased interaction with -Ser181 phosphorylated-KRAS (Fig 2).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…53 Most importantly, we recently reported that inhibition of KRAS phosphorylation impaired tumor growth. 54 This is in agreement with the data presented here as we show that the cell lines with higher interaction of oncogenic KRAS with p110α ( Fig S9) and with HNRNPA2B1 (Fig 2) were the ones harboring phosphorylated KRAS (Fig 6) at serumlimiting conditions. Related to this point, in the current work we also proved that KRAS phosphorylation at Ser181 was sufficient to recruit more HNRNPA2B1 to the cytoplasmic cell membrane (Fig 6), thus suggesting that the higher cytoplasmic accumulation that exhibited KRAS-dependent PDAC was a consequence, instead of a cause, of its increased interaction with -Ser181 phosphorylated-KRAS (Fig 2).…”
Section: Discussionsupporting
confidence: 93%
“…[52][53][54] HeLa cells were transfected with the oncogenic KRAS phosphomutants for Ser181 phosphorylation ("phosphorylatable" wild-type (S), non-phosphorylatable (A) or phosphomimetic (D)) and cell lysates were immunoprecipitated with anti-HA antibody. We found that HNRNPA2B1 interacted with the "phosphorylatable" (S) and exhibited an enhanced interaction with the phosphomimetic (D), while no interaction was seen with the non-phosphorylatable (A) KRAS phosphomutant ( Fig 6A).…”
Section: Hnrnpa2b1 Interaction With Kras Depends On Kras Ser181-phospmentioning
confidence: 99%
“…It was also reported that K-Ras with a phosphomimetic residue at position 181 induces apoptosis (84). These works point to the biological significance of K-Ras4B phosphorylation (83). Protein kinase C, a ligand of 14-3-3, mediates the phosphorylation at Ser-181 in the K-Ras4B HVR, which is believed to dissociate K-Ras4B from the plasma membrane through electrostatic repulsion with the negatively charged phospholipid headgroups (85)(86)(87) and Ras trafficking in the cytoplasm to an internal membrane (9).…”
Section: Membrane Binding Of Hvr K-ras4bmentioning
confidence: 80%
“…Our studies demonstrated that attachment of the phosphoryl group at Ser-181 in the HVR removes the farnesyl from the fluidic lipid bilayers even in the presence of the anionic phospholipids. Phosphomimetic mutant S181D, a mimetic of phosphorylation, enhances tumor growth (83). It was also reported that K-Ras with a phosphomimetic residue at position 181 induces apoptosis (84).…”
Section: Membrane Binding Of Hvr K-ras4bmentioning
confidence: 99%
“…KRAS4B is distinguished from other RAS isoforms in having a phosphorylation site (S181) within the HVR that acts as an electrostatic farnesyl switch, causing KRAS4B translocation from the plasma membrane to endomembrane compartments (Barcelo et al, 2014;Quatela et al, 2008) (see poster). This altered subcellular localization differentially influences effector engagement and biological activity of KRAS4B.…”
Section: Ras Isoform Differences and Post-translational Modificationsmentioning
confidence: 99%